TRAINING FOR THE MAKING OF NATURAL HERBAL SOAP AND CLAY MASK AS SOUVENIR PRODUCTS IN SUSUNAN BARU VILLAGE, BANDAR LAMPUNG - Yulyuswarni Yulyuswarni; Dias Ardini; Endah Ratnasari Mulatasih (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
Natural products such as natural soaps and clay masks are in high demand these days. These two products are possible as early entrepreneurial products in the field of souvenirs and home made cosmetics. The method of production and relatively affordable capital. Clay masks among the younger generation are the most sought-after masks, both because of their properties, how easy they are to use and affordable prices. Community service activities include an entrepreneurial open mind, counseling on the manufacture of natural herbal soap and claymask, as well as packaging of souvenir products. The results of pretest and posttest testing showed an increase in participants knowledge of 33%.